Data Management in Fog Computing - Nikoui, Tina Samizadeh; Rahmani, Amir Masoud; Tabarsaied, Hooman (Fog and Edge Computing, 2019)
Fog computing plays an important role in a huge and real‐time data management system for Internet of Things (IoT). This chapter focuses on data management in fog computing and proposes a conceptual architecture. It reviews fog data management and highlights the management issues. The chapter presents a number of studies that are done on fog data management. It discusses the main concepts of fog data management and the proposed architecture. The chapter addresses surveys and paper on fog computing architecture. Typical fog computing architecture has three basic layers: device layer, fog layer, and cloud layer. Data life cycle and fog data characteristics as the essential concepts of fog data management are elaborated. The chapter provides a conceptual architecture based on the three‐layer model to handle data management issues. It presents future research and directions, and addresses some key challenges that are related to data management issue.